1984
DOI: 10.1111/j.1600-0722.1984.tb00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of patients referred for investigation regarding so‐called oral galvanism

Abstract: – Fifty‐four patients referred to the Faculty of Odontology, University of Umeå, for investigation regarding “oral galvanism” were subjected to a general oral investigation. In addition the following parameters were studied: the highest calculated current between two metallic restorations in contact and the electrogustometrically determined threshold value for each person. No differences were found regarding these two parameters between the patients and a control group consisting of 15 persons. However, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
3

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
4
10
3
Order By: Relevance
“…This was also verified by the fact that 44% of the patients reported that they had chosen this type of therapy to avoid metallic restorations, compared with the 40% who had chosen it for esthetic reasons. That females are more negative to metallic restorations has been shown in several other studies (12)(13)(14) and is corroborated by our findings.…”
Section: Discussionsupporting
confidence: 95%
“…This was also verified by the fact that 44% of the patients reported that they had chosen this type of therapy to avoid metallic restorations, compared with the 40% who had chosen it for esthetic reasons. That females are more negative to metallic restorations has been shown in several other studies (12)(13)(14) and is corroborated by our findings.…”
Section: Discussionsupporting
confidence: 95%
“…The observed maximum corrosion current density of 0.3 |iA/cm-is 2-3 orders of magnitude lower than the values reported to elicit metallic or other unpleasant taste sensations in test persons (15). On the other hand, the marked covering of most of the surface of the brazed specimen with corrosion products, as compared to the small charge transfer recorded, suggests a significant activity of a local corrosion cell: The brazed joint corrodes anodically, releasing metal ions that combine with hydroxide and chloride ions in the electrolyte, precipitating as corrosion products on the cathodic surface of the rest of the specimen.…”
Section: Discussioncontrasting
confidence: 56%
“…Discussion JOHANSSON et al (17) reported in their study of oral galvanism patients that the patients' periodontal condition was worse, and they more often needed treatment for their stomatognathic or TMJ disorders than the controls. The same has been observed in other Swedish studies with patients complaining of symptoms related to oral galvanism (7,8) or amalgam fillings in general (9,10).…”
Section: Resultsmentioning
confidence: 97%